STUDENTS' PERCEPTION OF THE ABILITY TO ESTABLISH A BUSINESS AND ENTREPRENEURSHIP COURSES AS A SUPPORT FOR COMPETENCE - Arief Budiman (Jurnal MEBIS (Manajemen dan Bisnis), 2022)
This study aims to determine students' perceptions of the ability to establish a business and entrepreneurship courses to support student competence in establishing a business. This research uses qualitative methods to gain an in-depth understanding of data collection techniques through observation, documentation, and interviews with UPN Veteran Java student Timur taking an entrepreneurship course. The results of the analysis from the interviews that have been conducted state that 98% of the students interviewed have the desire to become an entrepreneur. Furthermore, the interview results stated that some factors hindered students from establishing a business, namely, in the first place, mentioning the factors that hinder financial factors. In second place mentions the inability factor in time management, and the rest in the third place is the fear factor in starting a business. the most decisive in establishing a business is the financial or capital factor. Furthermore, the study’s results stated that students perceive that the entrepreneurship course will later provide positive insights into their desire to become an entrepreneur. So that it can be concluded, it is necessary to have a theory related to entrepreneurship, direct practice related to business ideas, and intense assistance to each group that makes a business idea so that the idea can be adequately realized.